„Kukerzy” – przykład obrzędowości karnawałowej w Bułgarii - Zytka, Magdalena (Slavica Lodziensia, 2019)
The author analyses Bulgarian ritual called kukeri as an example of carnival rituals in Bulgaria. Special consideration is taken into history and description of the carnival processions and the meaning of the Pernik Festival to local community. In the first part the main goal is to present a special time of the year in that culture as well as the kukeri procession. In the second part, author presents similar ritual, called kurentovanje, that takes place in Slovenia and deals with finding the meaning of Festival to inhabitants of Pernik and the role of UNESCO list to spread the magic of fertility, success and wealthy of a human being to tourists around the world.